Effect of zinc supplementation on morbidity among stunted children in Indonesia - Rustam Siregar; Lilisianawati Lilisianawati; Endang Dewi Lestari; Harsono Salimo (Indonesian Pediatric Society, 2011)
Background The Indonesian Health Ministry reported that 35 .6%Â of Indonesian children and up to 50% in certain regions haveÂ stunted growth. They are at high risk of chronic zinc deficiency.Â Inadequate zinc intake may result in an impaired immune sy stemÂ and high incidence of morbidity. Zinc supplementation is knOtoÂ improve immune status thus reducing the incidence of morbidityÂ among stunted children.Objective To evaluate the effects of zinc supplementation onÂ morbidity incidence among stunted Indonesian school children.Â Methods We evaluated the effects of daily zinc supplementationÂ (2.38 mg of zincô€‡supplemented milk) on the incidence of diarrhea,Â respiratory infections, and fever in a doubleô€‡blind, randomized,Â controlled trial in 169 stunted children (zincô€‡supplementedÂ n=84; placebo n=85) aged 7 to 9 years in Jakarta and Solo. Zincsupplementation and morbidity surveillance were perfonned forÂ 6 months.Results Compared to the first 3 months of intervention, zincÂ supplementation resulted in a reduction in the incidence ofÂ diarrhea, respiratory infections, and fever during the second threeÂ months (by 67%, 42%, and 30%, respectively). Children fromÂ the zincô€‡supplemented group tended to have a lower episodicÂ incidence of diarrhea and fever than those from the placebo group,Â although neither of these differences was statistically significant (P< 0.45,95% CI 0.63 to 0.89).Conclusion Zinc supplementation has no significant effect inÂ reducing the incidence of diarrhea, respiratory infections, andÂ fever in stunted children although tended to have a lower episodicÂ incidence.Â